2022
DOI: 10.3390/diagnostics12102352
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Clinical Arch Forms in Iraqi Population: A National Survey

Abstract: This study aims to identify mandibular clinical arch forms and dimensions in the Iraqi population. Materials and methods: The study sample consisted of pre-treatment mandibular study models of the Iraqi population. The most labial aspect of 13 proximal contact areas was digitized using AutoCAD software to determine the clinical bracket point for every tooth. The dental arches were classified into three types: tapered, ovoid, and square. The arch dimensions were identified using four linear and two proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…We rejected the null hypothesis, as there was a significant difference in males with SCA. In females, there was no significant difference between the control group and the SCA group as the tapered arch was prevalent in both groups and this agrees with Ali and Yassir,[ 40 ] who found a higher percentage of tapered arches in normal Iraqi females [ Figures 7 and 8 ].…”
Section: Discussionsupporting
confidence: 84%
“…We rejected the null hypothesis, as there was a significant difference in males with SCA. In females, there was no significant difference between the control group and the SCA group as the tapered arch was prevalent in both groups and this agrees with Ali and Yassir,[ 40 ] who found a higher percentage of tapered arches in normal Iraqi females [ Figures 7 and 8 ].…”
Section: Discussionsupporting
confidence: 84%
“…Human malocclusion is a displacement of the teeth and jaws that can impair the quality of life and cause altered facial features, reduced masticatory efficiency, and an increased risk of teeth destruction (1) . Dental arches can vary in size and shape based on the various ethnic and racial groups' exposure to various environmental variables, genetic background, and developmental traits (2) . Numerous genetic and environmental factors that occurred at various gestational stages contributed to a variety of malformations in the dentofacial and craniofacial structures (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al carried out a national survey to analyze clinical arch forms and dimensions in the Iraqi population [8]. The results showed that the males' linear measurements were more significant based on collecting the 1005 pre-treatment mandibular models.…”
mentioning
confidence: 99%